150 Neurocognitive Development of Children Four Years after Critical Illness and Treatment with Tight Glucose Control: A Randomized, Controlled Trial. (October 2012) - Gielen, M; Mesotten, D; Sterken, C; Claessens, K; Hermans, G; Vlasselaers, D; Lemiere, J; Lagae, L; Gewillig, M; Eyskens, B; Vanhorebeek, I; Wouters, PJ; et al.
Abstract : Background and aims: The first large RCT on tight-glucose-control (TGC) to age-adjusted normoglycemia in the pediatric-intensive-care-unit (PICU) (Vlasselaers 2009) revealed that TGC reduced PICU morbidity and mortality as compared with usual-care, but increased hypoglycemia ≤40 mg/dL. As both hyper- and hypoglycemia may adversely affect the developing brain, an assessment of long-term neurocognitive function was required to exclude harm and validate any short-term benefit of TGC. Methods: Follow-up of all 700 patients included in the original RCT, was performed 4 years after randomization. Death or disability precluding neurocognitive testing were a priori defined as poor outcomes. The primary endpoint was full-scale IQ, assessed with age-adjusted intelligence-tests (Wechsler-IQ-scales). Neurodevelopmental-testing also encompassed a neurological examination, and tests for visual-motor-integration (VMI-Beery-Buktenica-Developmental-Test), attention and executive functions (ANT-Amsterdam-Neuropsychological-Tasks), memory (Children's-Memory-Scale), and behavior (Child-Behavior-CheckList). For comparison, 216 healthy siblings and unrelated children were tested. Results: At follow-up, TGC in PICU had not increased the incidence of poor outcomes [19% vs.18%, univariable OR for poor outcome with TGC 1.10 (0.76–1.62), P =0.6]. Sixteen percent of the 700 ICU patients declined participation or were not contactable. TGC did not affect full-scale IQ [median 88.0 (IQR 74.0–100.0) vs. 88.5 (74.3–99.0), P =0.7], nor other scores for intelligence, visual-motor-integration, memory and behavior. TGC actually improved motor coordination (all P ≤0.03) and cognitive flexibility ( P =0.02), the latter up to the level of healthy children. Imputation for missing values confirmed these results. Hypoglycemia evoked by TGC did not negatively affect neurocognitive outcome. Conclusion: Despite hypoglycemia, TGC in PICU did not harm neurocognitive development 4 years later.